A Technique to Increase Accessibility to Late‐Stage Chick Embryos for In Ovo Manipulations. Issue 2 (22nd January 2013) - Spurlin, James; Lwigale, Peter
<x xml:space="preserve">Abstract</x> Background: During early development, avian embryos are easily accessible in ovo for transplantations and experimental perturbations. However, these qualities of the avian embryonic model rapidly wane shortly after embryonic day (E)4 when the embryo is obscured by extraembryonic membranes, making it difficult to study developmental events that occur at later stages in vivo. Results: In this study, we describe a multistep method that involves initially windowing eggs at E3, followed by dissecting away extraembryonic membranes at E5 to facilitate embryo accessibility in ovo until later stages of development. The majority of the embryos subjected to this technique remain exposed between E5 and E8, then become gradually displaced by the growing allantois from posterior to anterior regions. Conclusions: Exposed embryos are viable and compatible with embryological and modern developmental biology techniques including tissue grafting and ablation, gene manipulation by electroporation, and protein expression. This technique opens up new avenues for studying complex cellular interactions during organogenesis and can be further extrapolated to regeneration and stem cell studies. Developmental Dynamics 242:148–154, 2013. © 2012 Wiley Periodicals, Inc.